Dimensions of Hamka's Modern Sufism (A study of the verses of Maqamat in Tafsir Al-Azhar by Hamka) - Zulkifli Zulkifli; M. Daud Rhosyidy (Jurnal Studi Al-Qur'an, 2024)
Seeing the reality of today's society, moral degradation has arisen in humans, so it is essential to improve ourselves by returning humans to their existence as servants of Allah SWT. One alternative is to study and practice the teachings of Sufism. In the teachings, there are spiritual stages (maqâmât) to achieve perfection as a servant of Allah. The focus of this research is to examine Hamka's interpretation style in al-Azhar's tafsir by explaining his interpretation regarding the maqâmât verses so that the dimensions of Sufism and its relevance found in Hamka's al-Azhar tafsir are known. This research aims to find out Hamka's style and interpretation in al-Azhar's interpretation regarding the maqâmât verses and the dimensions of Sufism contained in them so that we can find out whether maqâmât is still relevant or not to be practiced in the present era. The methodology used in this research is qualitative library research (library research) with a mauḍu'i model of the Sufism approach that focuses on maqâmât verses using descriptive-analytical analysis of Hamka's Sufism thought. The results of this discussion show thatHamka's interpretation of the verses of maqâmât is in the style of Sufism by exploring the meaning of zahir and theinner meaning in which there are nuances to society (Adabi Ijtima'i) covering the socio-culture of Indonesianculture so that the dimension of Sufism contained in Hamka's interpretation is still very relevant to modern lifetoday.